Pendidikan Islam Multikultural untuk Moderasi Beragama sebagai Kapital Kebangkitan Peradaban Indonesia - Jauhari, Moh. Irmawan; Wahyudi, Ahmad (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2022)
The decline of Islam starting in the 13th century due to various complex problems. When the dialectical pendulum of civilization points back to Islam as a cultural form which is the antithesis of the West, then the real opportunity for Islam to rise is very large. In this case, Islam in the Archipelago with a series of patterns and models can be considered for further photographing the map of the revival of Islamic civilization in Indonesia. Considering today's era of informatics, a culture that is accommodative, flexible, and able to adapt to the rapidly rotating historical movement is needed. The nature of Islam Nusantara has a tendency to be moderate, tolerant and open. It is very different from the character of Arab and Middle Eastern Islam, which today are experiencing internal divisions. The main focus of the first article, tries to elaborate further on Multiculturalism Islamic Education as the capital of civilization. Three important elements in educational institutions that can be done to convey the mission of Multicultural Islamic Education. The paradigmatic view of educational institution managers in developing multicultural education in schools/madrasahs, curriculum structures and educational activities that offer multicultural values ​​to students, and school/madrasah cultures that support multiculturalism values. Second, Sufism as the root of moderation shows the historical facts of Islam that can be accepted by all levels of society so that it then forms the character of the Islamic Archipelago which is moderate and diverse in culture. Third, moderate Islam as the foundation of social cohesion tries to reflect and reinterpret Gus Dur's ideas to build a harmonious relationship by developing the concept of contextual fiqh. Where by practicing the norms of fiqh as a whole and contextually based on ability, besides fiqh will develop, it will also be able to build social cohesion for the sake of the progress of Indonesian civilization.